Optimization of dual duct forced auxiliary ventilation system to mitigate particulate matter emissions in a polymetallic underground mine environment: A hybrid approach - Abdullah Rasheed Qureshi; Sergei Sabanov; Emil Bayramov; Jessica Neafie (PLoS ONE, 2025)
The auxiliary ventilation system (AVS) is essential for managing airflow and reducing particulate matter (PM) levels in underground mine environments. Despite its importance, prior studies have insufficiently examined the optimal design of dual duct forced (DDF) AVS to improve airflow and PM management during the loading and unloading operations of diesel-powered equipment (DPE). This work addresses the research gap by utilizing a hybrid methodology to assess the effectiveness of four DDF-AVS designs (1–4) under two distinct DPE operating scenarios: (S1) DPE loading beside the working face and (S2) DPE unloading at a temporary dumpsite. The study utilized Ansys-Fluent for numerical simulations and revealed the following conclusions: the airflow field within the drift displays intricate patterns that substantially affect PM transport; S2 presents the greatest potential PM exposure danger to DPE operators, succeeded by S1. Among the designs, AVS 2 and AVS 3 exhibited efficiency by less complicated airflow patterns and optimal PM transposition within the drift. In comparison to AVS 1, the PM dispersion enhanced by 15.66% and 7.83% in S1, whereas in S2, it improved by 27% and 46% under AVS 2 and AVS 3, respectively. This research study offers significant insights for optimizing AVS designs, minimizing PM exposure to miners, and improving the underground mine environment through cleaner production techniques.